40th Structures, Structural Dynamics, and Materials Conference and Exhibit 1999
DOI: 10.2514/6.1999-1252
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric flight gust loads analysis

Abstract: Public reporting burden for this collection o( information is estimated to average 1 hour per response, including the time tor reviewing instructions, searching existing data sources, gathering and mantaining the data needed and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, 'to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The program was used to develop 24 sets of forcing functions that were used in the Monte Carlo gust analysis described in Ref. 15. 1 1 1 1 1 1 j 1 1 1 1 1 1 1 1 1 | Tl 11 T I M 1 I 1 1 1 1 1 1 1 1 1 [ 1 1 1 1 1 1 1 1 1 | 1 1 1 1 1 1 1 1 1 3300 '<%?…”
Section: Resultsmentioning
confidence: 99%
“…The program was used to develop 24 sets of forcing functions that were used in the Monte Carlo gust analysis described in Ref. 15. 1 1 1 1 1 1 j 1 1 1 1 1 1 1 1 1 | Tl 11 T I M 1 I 1 1 1 1 1 1 1 1 1 [ 1 1 1 1 1 1 1 1 1 | 1 1 1 1 1 1 1 1 1 3300 '<%?…”
Section: Resultsmentioning
confidence: 99%
“…15) required each filtered wind profile to be restricted to an altitude band of 6000 ft. To minimize step responses during the gust loads simulations, a flattop window having a ten percent cosine taper at each end was used (Fig. 8c).…”
Section: Restriction To 6000-ft Bandsmentioning
confidence: 99%
“…a) Two-point smoothed wind and trend removed for X G = 4200 ft; b) High-passed filtered wind profile 33 15. a) Two-point smoothed wind and trend removed for X G = 4700 ft; b) High-passed filtered wind profile 34 16.…”
mentioning
confidence: 99%
“…(14) are necessary to develop empirical gust loads analysis forcing functions 2 " and to establish loads due to atmospheric turbulence. 21 ' 22 Since the gust loads analysis accounts for the turbulent components of the winds statistically, and the average boundary between the slowly-varying and turbulent components of the wind can now be defined for the ER and WR ranges, there is the possibility of retaining in the day-of-launch loads analyses only those components of the winds that are slowly varying. 21 It is suggested that, to conservatively bracket the variation of this function, the values obtained with Eq.…”
Section: Potential Usesmentioning
confidence: 99%